Political parody: The new image of Mongolian contemporary art - Naidansuren, Ochirbat (Curtin University, 2015)
This research investigates the paradigm of parody in Mongolian political art through exploring its connection with the mythological figure of the manggus. As it has emerged in the Mongolian visual art of parody, the manggus figure incarnates various fears. Fundamental to this exegesis is researching the national sensibility for using parody in Mongolian art as a response to fear and as a mode of resistance-this is a new investigation in academic scholarship into Mongol identity and art.